Study of the use of agile methodologies in the development of software construction projects in Colombia (2018)
The Software Engineering Research Group of the University Francisco de Paula Santander has been implementing projects based on the development of methodologies for the creation of software; thus, as part of these projects a study of the use and knowledge of Agile Methodologies was conducted. The study was based on the application of a survey to determine the preference of IT professionals in identifying the most agile methodologies used in development groups in Colombia and to determine the selection criteria. The survey was applied to a sample of one hundred and four (104) professionals from a population of one thousand two hundred and thirty-four (1234) Systems Engineers; graduates from the Systems Engineering program who work as developers throughout the country. From the study, it can be concluded that Colombia is keeping up with global trends in the use of Agile methodologies; as a result, 73% of the professionals surveyed applied an agile methodology for the development of software products and of the percentage obtained, 43.42% used the Scrum methodology and 19.7% applied the Scrum/XP hybrid.